Immune Thrombocytopenic Purpura Refractory to Corticosteroid Therapy in pregnant women: A literature review (Research, Society and Development, 2025)
Introduction: Immune Thrombocytopenic Purpura is defined as a platelet count below 100x109/L marked by signs of spontaneous bleeding. It is a pathology frequently observed in pregnant women. The pathophysiology is a reaction of autoantibodies that bind to platelet membrane proteins. The diagnosis is made by exclusion and confirmed by the response to therapy. It presents as a challenge during prenatal care and current guidelines present treatment protocols based on expert opinions and results of retrospective studies. Method: Narrative review of literature based on the data platforms: Scielo and PubMed. Inclusion and exclusion criteria were applied, totaling 34 articles discussed here. Results and Discussion: The management of Immune Thrombocytopenic Purpura is quite complex, with oral corticosteroids and immunoglobulins as the first line. Patients who are refractory to first-line treatment may use TPO receptor agonists, which have shown good results in published case reports, retrospective studies, and experimental studies in animals. Splenectomy is also a second-line therapeutic option but presents greater risks when performed in pregnant women. Conclusion: Immune Thrombocytopenic Purpura may present resistance to first-line treatment, and treatment protocols for resistant pregnant women are scarce. Among the second-line therapeutic options, the use of Thrombopoietin Receptor Agonists stands out, and the less recommended, splenectomy. Clinical trials with second-line therapies and treatment protocols for corticosteroid-resistant pregnant women are recommended.